Effect of some local compost mixtures and nitrogen fertilizer on the growth, yield and oil content of marjoram (Origanum majorana L.) plant - Hammo, Yousif Hussen; Lazim, Zainab Sabah; Ahmad, Zhala Muhammad (Sulaimani Journal for Pure and Applied Sciences, 2018)
This factorial experiment was carried out during spring season 2014 at the Department of Horticulture, College of Agricultural Sciences, University of Sulaimani, to study the influence of three concentrations of nitrogen fertilizer (0, 100, 200 mg.L-1N) and four kinds of growing media (A1=100% river soil without local composet), (A2= 25% local compost: 75% river soil), (A3= 50% local compost: 50% river soil) and (A4=75% local compost: 25% river soil) on the growth, yield and volatile oil of Majoram (Origanum majorana L). The experiment was conducted in Randomized Complete Block Design with three replications; means were compared according to Duncan’s test (P≤0.05). The results showed that plants fertilized with(100 and 200 mg.L-1N) gave significant increases in plant high, growth index, vegetative dry weight, volatile oil percentage, volatile oil yield and (N%, P%, K%) compared to the control. On the other side, the plants that planted in A3 and A4 media showed significant increases in plant height, growth index, vegetative dry weight, root dry weight, volatile oil percentage, volatile oil yield and (N%, P% and K%) compared to A1 and A2. Regarding to the interaction between nitrogen fertilization and media there were significant effects on all vegetative characters and chemical characters, especially the effect of combinations between 100 mg.L-1N and A3 composed media (50:50 local compost + river soil).Which was predominated all other combinations.
Keywords: Origanum majorana L Nitrogen fertilizer Local compost